Ein Beitrag zur Entwicklung von einheitlichen Entwurfslösungen für Hochleistungsstraßen in urbanen Gebieten. - Schmitt, Dominik (My University, 2019)
Im deutschen Straßennetz existieren Hochleistungsstraßen, die sowohl dem Fernverkehr dienen als auch innerstädtische Verkehre auf sich ziehen und damit das nachgeordnete Straßennetz entlasten. Dabei verfügen diese Straßen, die hohe Verkehrsmengen abwickeln und entweder urban oder autobahnähnlich gestaltet sind, über breite Straßenquerschnitte mit mindestens vier Fahrstreifen in beiden Fahrtrichtungen. Hochleistungsstraßen sind dabei keine eingeführte Kategorie in den Regelwerken der Forschungsgesellschaft für Straßen- und Verkehrswesen und entsprechende Entwurfsempfehlungen existieren bislang nicht. Die im Bestand zu verzeichnenden Entwurfselemente weichen teilweise erheblich von den derzeit gültigen anerkannten Regeln für bestehende Kategorien von Stadtstraßen oder Autobahnen ab. Wesentliche Aufgabe der Arbeit ist die Entwicklung von geeigneten Entwurfsparametern für Hochleistungsstraßen, die die Anforderungen der Verkehrssicherheit, der Fahrtgeschwindigkeit, des Lärmschutzes sowie der städtebaulichen und stadtplanerischen Qualität möglichst weitgehend erfüllen. Auf Basis einer Literaturanalyse erfolgte zunächst die Entwicklung einer Begriffsdefinition von urbanen und autobahnähnlichen Hochleistungsstraßen. Darauf aufbauend wurde eine Befragung von Städten mit mehr als 200.000 Einwohnern zu Straßen dieses Typs durchgeführt. Festzuhalten ist, dass zahlreiche Hochleistungsstraßen in vielen Städten wesentlicher Bestandteil des Straßennetzes sind. Auf Grundlage der Befragung der Städte wurde ein Untersuchungskollektiv von 13 Hochleistungsstraßen für weiterführende Detailanalysen ausgewählt. Durch die Detailanalysen konnten Erkenntnisse zu den verschiedenen Analyse- und Wirkungsbereichen gewonnen werden. Dabei war grundsätzlich festzustellen, dass Hochleistungsstraßen ihre Verkehrs- und Erschließungsfunktion weitestgehend leistungsfähig und sicher erfüllen. Die entwickelten Entwurfsparameter und Empfehlungen sollen dazu beitragen, den bislang nicht existenten Straßentypus der Hochleistungsstraße in die Regelwerke einzuführen, wobei neben verkehrlichen Belangen auch städtebauliche sowie stadtplanerische Aspekte berücksichtigt werden sollten.

In Germany, there are high capacity roads which are used by long-distance traffic and local traffic while relieving the subordinate road network. The cross-section of these roads which are designed urban or motorway-like consists of at least two lanes per direction of travel, which enable them to handle high traffic volumes. High capacity roads are not a category in the existing guidelines of the German “Road and Transportation Research Association” and therefore there are no corresponding design recommendations. The existing design elements in some cases differ significantly from the currently valid rules for existing categories of urban streets or motorways. The main task of this research project was the development of design parameters for high capacity roads in consideration of traffic safety, travel speed, noise protection measures as well as aspects of urban development and urban planning. At first, a terminology for urban and motorway-like high capacity roads was developed based on a literature research. On this basis, a survey on roads of this type was conducted among German municipalities with more than 200.000 inhabitants. It was determined that a large number of high capacity roads exist in the German road network. On the basis of the survey of the municipalities, a research collective of 13 high-speed lines was finally selected for further detailed analyses. The detailed analyses provided insights into the different areas of analysis and impact. It was recognizable that high capacity roads fulfill their traffic and development functions as far as possible efficiently and safely. Elevated intersections proved to be more beneficial compared to non elevated intersections regarding the analyses of the travel speed and traffic safety. It should be noted that at elevated intersections the pedestrian and bicycle traffic is often relocated to the surrounding road network and thus, compared to non elevated intersections, no corresponding effects on the travel speed and traffic safety occurred. However, if aspects of accessibility for road users of non-motorized individual traffic, urban planning integration or noise protection aspects are consulted, non elevated intersections are more suitable than elevated ones. Priority-controlled intersections and land accesses with low traffic volumes did not adversely affect the traffic speed or the traffic safety of high capacity roads. Furthermore there were no negative aspects of accessibility for road users of the non-motorized individual traffic and urban integration. When considering the noise emissions of high capacity roads, closed buildings with more than three floors also proved to be suitable, also with regard to urban planning aspects, for shielding the down-stream areas. The developed design parameters and recommendations were intended to introduce the so far non-existent road type of the high capacity road into the existing guidelines of the German “Road and Transportation Research Association” taking into account not only transport issues but also urban planning and urban development aspects.
Design parameters for high capacity roads within built up areas .
Keywords: Verkehr; Großstadt; Integrierte Verkehrsplanung; Stadtautobahn; Durchgangsverkehr; Fernverkehr; Straßengestaltung; Erschließungsstraße; Ausbaustandard; Entwurfsparameter; Verkehrssicherheit; Umweltbelastung; Geschwindigkeit; Straßenverkehrslärm; Empfehlung; Hochleistungsstraße